The Role of Complement in Organ Transplantation - Grafals, Monica; Thurman, Joshua M. (Frontiers in Immunology, 2019)
The current immunosuppressive protocols used in transplant recipients have improved short-term outcomes, but long-term allograft failure remains an important clinical problem. Greater understanding of the immunologic mechanisms that cause allograft failure are needed, as well as new treatment strategies for protecting transplanted organs. The complement cascade is an important part of the innate immune system. Studies have shown that complement activation contributes to allograft injury in several clinical settings, including ischemia/reperfusion injury and antibody mediated rejection. Furthermore, the complement system plays critical roles in modulating the responses of T cells and B cells to antigens. Therapeutic complement inhibitors, therefore, may be effective for protecting transplanted organs from several causes of inflammatory injury. Although several anti-complement drugs have shown promise in selected patients, the role of these drugs in transplantation medicine requires further study.